ON THE ASYMPTOTIC-BEHAVIOR OF OPTIMAL ROOT LOCI - Kouvaritakis, B (1981)
Optimal root loci have received some attention in the recent literature. Results concerning the state space characterization of optimal root loci, however, either deal with lower-order behavior only or apply to a restricted class of (A, B, C) state space models. The present paper develops a simple algorithm which deals with the state spce characterization of all orders of optimal root locus behavior and which applied to any system (A, B, C).